(untitled) (Journal of Solar Energy Research Updates, 2024)
An efficient and low-cost Selective Solar Absorber for integral ceramic solar collectors, based in glazes pigmented with t-CuCr2O4 and Sb modified t-CuCr2O4 pigments, are characterised and evaluated. The basic kinds of industrial glazes (soda lime glass, double firing glaze 1050 ºC and both single firing glazes of 1080 ºC and porcelain glaze of 1190 ºC) have been checked and characterised by CIEL*a*b* colour, UV-Vis-NIR diffuse reflectance spectra, bandgap measurements, SEM-EDS analysis and solar absorbance spectra. The characteristics of the black powders (L*a*b* and diffuse reflectance spectra with a deviation from the carbon black ΔE*=20.3 and 22.3 respectively) are improved in 0.5 wt% addition of pigments in soda lime glass (ΔE*=6.1 and 9.9 respectively) and in 5 wt% glazed in porcelain glaze 1190 °C (ΔE*=12.0 and 18.4 respectively) which can be considered as low-cost selective solar absorbers (SSA) for integral solar absorber collectors.